'¿How much do your hands cost?': Complexifying the occupational risk prevention of Barcelona’s construction sector - Garcia Curado, Xavier (Revista de Antropología Social, 2021)
Historically, the construction sector has been intensive in labor force. Still today, the workers bodies remain as the main source of value creation in this sector. Because of that, the tension between productivity and health is strongly integrated in the mode of production. This article is based on an ethnographic research carried out in Barcelona, we aim to show that the application of certain labor prevention laws and the 2007 economic crisis creates a scenario which allows us a great analytical opportunity to observe how the risks are culturally perceived and how workers manage these risks in everyday practices. This context also allows applying a critical focus on the current epistemological framework from which risk and accidents are conceived. This framework is based on the individualization, rationalization, objectivation and commodification. As an alternative, I am going to propose a focus that rests on the notion of power, then, we will point out some processes of risk assumption that, normally, remain invisibilized.
Keywords: construction; workers; risks; health; power